2014
DOI: 10.5430/cns.v3n1p100
|View full text |Cite
|
Sign up to set email alerts
|

Nurse practitioner role in home healthcare: Challenges and opportunities

Abstract: Home health agencies must follow Medicare's conditions of participations, as well as federal requirements with regard to plans of care and payment. Federal laws mandate that home health agencies can not authorize nurse practitioners (NPs) to direct patient care in the home environment. Instead, all orders must be signed by a physician or Medicare reimbursement may be jeopardized. Removing this barrier to care and supporting legislation that allows nurse practitioners to write orders and manage the care of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…For example, organizational regulations in certain care settings (e.g., nursing homes or home care) can limit NPs’ ability to practice independently regardless of the level of state NP practice regulations. Despite FPA, NPs still need a physician’s signature on home care orders due to federal billing regulations (Chicoine & Aselton, 2015; Wolff-Baker & Ordona, 2019). Future research could also be conducted using more robust study designs, such as natural experiments (e.g., difference-in-differences designs) or retrospective cohort study designs with longitudinal datasets to assess the impact of regulatory changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, organizational regulations in certain care settings (e.g., nursing homes or home care) can limit NPs’ ability to practice independently regardless of the level of state NP practice regulations. Despite FPA, NPs still need a physician’s signature on home care orders due to federal billing regulations (Chicoine & Aselton, 2015; Wolff-Baker & Ordona, 2019). Future research could also be conducted using more robust study designs, such as natural experiments (e.g., difference-in-differences designs) or retrospective cohort study designs with longitudinal datasets to assess the impact of regulatory changes over time.…”
Section: Discussionmentioning
confidence: 99%
“…Dudenstadt found that nurse practitioners in adult home care have an additional role [11]. Cicoine showed that nurse practitioners in homecare provide quality patient care [12]. Patients were more able to manage their own disease and focused increasingly on their health and self-regulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, international literature also suggests that previous nursing experience as well as mentoring by preceptors who provide clinical supervision is crucial for novice NPs to develop the skills and competencies (e.g. history taking, physical examination, clinical reasoning, and care planning) required to provide health services such as home visits autonomously and with high quality (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%